Summary of the 1st International Workshop on Environmental, Safety and Economic Aspects of Fusion Power. (6th September 2016) - Wu, Y.; Stevens, E.; Kim, K.; Maisonnier, D.; Kalashnikov, A.; Tobita, K.; Jackson, D.; Alejaldre, C.; Perrault, D.; Panayotov, D.; Merrill, B.; Grisolia, C.; et al.
Abstract: The 1st International workshop on Environmental, Safety and Economic Aspects of Fusion Power (ESEFP) was held on 13 September 2015 at Jeju Island, South Korea. The workshop was initiated by the International Energy Agency Implementing Agreement on a Co-operative Program on ESEFP. The workshop was well attended with about forty participants representing twelve institutions in ten countries. The presentations covered safety issues and environmental impacts, availability improvement and risk control and socio-economic aspects of fusion power. Safety and licensing gaps between DEMO and ITER were discussed in depth with the consensus output presented as a plenary presentation at the 12th International Symposium on Fusion Nuclear Technology (ISFNT-12). The next workshop is planned to be held in conjunction with the ISFNT-13 in 2017.